Note from the editor: Body, virus, morals, and scandals - Ákos Róna-Tas (economic sociology_the european electronic newsletter, 2020)
This issue centers on the encounter between the economy and the human body. Economics, like other social sciences, treats people mostly as disembodied actors who never catch viruses or suffer from back pain or creeping dementia. These abstract actors are all too often assumed also to be immortal, rarely acting with an acute consciousness of a finite life. These issues become visible in our academic looking glass only when they emerge as social problems, not as the normal experience of everyday existence.
Keywords: 300